Developing of Village’s Heritage Tourism Planning Through Integrated of Foodscape and Landscape Architecture at Lahat Regency - Prima, Listen; Lussetyowati, Tutur; Adiyanto, Johannes (Sinektika: Jurnal Arsitektur, 2024)
The complex potential of villages provides a significant chance for local development. Commonly, the potential is developed as a single sector in each village through a separate program of relevant institutions. Lahat Regency is one of the regencies in South Sumatera Province, which has enormous local potential within the district, both material (natural resources, traditional houses, foods, etc.) and immaterial heritage (history, culture, traditions, etc.). These components of cultural heritage wealth will contribute to regional development and Indonesian identity. Among these districts, the Government of Lahat Regency focuses on Pulau Pinang District, particularly Tanjung Sirih and Lubuk Sepang Villages, as integrated tourism villages. This research aims to establish a development planning model by establishing integrated tourism planning, The integration not only unites two villages, Tanjung Sirih Village and Lubuk Sepang Village, in one location perspective related to their close geographical location, but also programs in local tourism themes based on the dominant potential, Tanjung Sirih with its foodscape and Lubuk Sepang with its landscape. Foodscape is an integration between food, people and environment, while landscape architecture is the human and environmental components. The research used qualitative research methods with local potential analysis and development area modeling; several variations of tools were used, such as literature work, surveys, and discussions. The reasearch output is an input for the tourism village integration in Lahat Regency as a development planning model and the foundation of potential tourism village development programs in Indonesia.